In-situ TEM study of loop evolution in FeCrAl alloy under Fe+ irradiation: Effects of temperatures, dislocations and precipitates - Kefei Pei; Guang Ran; Yipeng Li; Ziqi Cao; Dewang Cui; Ruiqian Zhang; Gang Yang (Nuclear Analysis, 2022)
Fe13.5Cr4.7Al alloy was irradiated in-situ with 400 keV Fe+ in TEM at RT and 748 K. The evolution of dislocation loops under the influence of temperatures, irradiation dose, dislocation lines and precipitates were characterized in detail. The loop rafting was found at RT irradiation for the first time and the growth direction of the rafted loops was along g = 110 direction. However, this phenomenon was not observed at 748 K and only the dislocation complex was appeared. The formation conditions of loop rafting were low temperature and a certain value of irradiation dose. The average size and number density of dislocation loops as a function of irradiation dose in the regions with dislocation lines, precipitates and no dislocation lines/precipitates were constructed and analyzed comparatively. At the same irradiation dose, sample irradiated at higher temperature has larger average loop size and lower loop number density. There was a complex interaction between dislocation line-loop at 748 K, but few interactions were observed at RT. At any irradiation dose, the loop number density in the region with dislocation lines was smaller than that in the region without dislocation lines, but the average loop size was slightly opposite. Moreover, the higher the irradiation temperature, the more obvious the effects of precipitates and dislocation lines on loop evolution were. Our current results provide a fundamental insight into how the dislocations, precipitates and dose affect loop evolution and characteristics in FeCrAl alloy at elevated temperatures.